Understanding Smoking Behavior among Physicians in Riyadh, Saudi Arabia: A Cross-Sectional Study - Abeer S. Al Shahrani; Najd R. Almudaiheem; Esraa M. Bakhsh; Nora T. Sarhan; Fay S. Aldossari; Budur A. bin Huzeim (SAGE Publishing, 2021)
Background: The prevalence of smoking has increased in recent years in Saudi Arabia. Our objectives were to determine the factors affecting smoking among physicians and to assess physicians' quitting behavior. Methods: A cross-sectional study was carried out at 3 district hospitals in Riyadh, Saudi Arabia. It involved physicians with different levels of experience and different specialties. They were asked to complete a self-administered questionnaire adapted from validated tools. The questionnaire addressed sociodemographic data, lifestyle, and work-related factors as well as smoking cessation and relapse. SPSS statistical software was used for the statistical analysis. Results: The study included 290 physicians, of whom 91% were Saudi and 59.7% were male. About 55.2% were younger than age of 30. Overall, 34.8% were smokers. The following factors had a significant association with smoking: a smoking family member/friend, resident occupational status, medical specialty, and frequent on-call duties increased the likelihood of smoking. One-third of the physicians (31.6%) who tried to quit smoking reported seeking information on social media, television, and/or the internet. The most common causes of relapse were social stress and withdrawal symptoms, while the least common was work-related stress. Conclusions: Smoking was highly prevalent among physicians. The likelihood of smoking was higher in, residents, medical specialists and those with a high number of on-call duties. Moreover, this study described cessation practices in this group, which might be considered when designing and improving counseling programs for physicians who smoke.